In vitro analysis of human immune response (IgG) against salivary gland extract of dengue vector from dengue hemorrhagic fever (DHF) endemic area in Jember, Indonesia. Issue 1 (November 2021) - Oktarianti, R; Damara, D R; Qudsiyah, S U R; Wathon, S; Senjarini, K
Abstract: The mosquito species Ae. aegypti and Ae. albopictus are two potential vectors of dengue fever. The salivary glands of these species contain substances that play a role in the transmission of pathogens. These include vasodilators and immunomodulatory compounds. Immunomodulatory components can modulate the host immune system by producing specific antibodies (IgG). This study aims to investigate the human immune response (IgG) against the salivary gland extract of Ae. aegypti and Ae. albopictus . Samples were collected from individuals who were Dengue patients, as well as healthy individuals and neonates from the Jember endemic area. Results show that the levels of IgG response vary across the individual. Generally, Dengue patients and healthy people in the DHF-endemic area had higher levels of IgG. The highest immune response was found in DHF patients, followed by healthy persons, and finally the neonate samples, respectively.